Fallen - Kate, Lauren (New York : Delacorte Press, 2009)
Suspected in the death of her boyfriend, seventeen-year- old Luce is sent to a Savannah, Georgia, reform school where she meets two intriguing boys and learns the truth about the strange shadows that have always haunted her.
Keywords: Supernatural -- Fiction; Reformatories -- Fiction; Schools -- Fiction; Love stories; Reincarnation -- Fiction; Angels -- Fiction; Savannah (Ga.) -- Fiction